2013
DOI: 10.1097/iop.0b013e31829bb162
|View full text |Cite
|
Sign up to set email alerts
|

Management of Congenital Nasolacrimal Duct Obstruction—Latin American Study

Abstract: The members of Ojoplast adopt massage as the initial treatment for congenital nasolacrimal duct obstruction for patients <1 year of age. Probing is performed on patients >1 year of age, and early probing is used only for cases of dilated lacrimal sac. When massage and probing are not effective, intubation is performed, and if intubation is unsuccessful, dacryocystorhinostomy is performed, in which the external approach to dacryocystorhinostomy is used most often.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…A study (10) of oculoplastic surgeons reported that 31% of respondents recommended massage until 6 months of age, which is similar to our result of 36.6% of respondents. However, 14.63% of pediatricians in our survey instructed the parents to perform a sac massage until 12 months of age, similar to a survey of oculoplastic surgeons (12%) (10). Higher rates were reported in surveys of pediatric ophthalmologists (82%) (13) and general ophthalmologists (84%) (3).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A study (10) of oculoplastic surgeons reported that 31% of respondents recommended massage until 6 months of age, which is similar to our result of 36.6% of respondents. However, 14.63% of pediatricians in our survey instructed the parents to perform a sac massage until 12 months of age, similar to a survey of oculoplastic surgeons (12%) (10). Higher rates were reported in surveys of pediatric ophthalmologists (82%) (13) and general ophthalmologists (84%) (3).…”
Section: Discussionsupporting
confidence: 90%
“…Although most cases of CNLDO resolve spontaneously within the first year of life, some may persist and cause significant distress to the child, parents, and pediatrician (2, 10, 11). Thus, a proper therapeutic strategy for CNLDO is essential for primary care providers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 However, perforation may still occur until the 12th month of life. 5,6 aLDO is due to a primary idiopathic or secondary inflammatory stenosis following trauma, neoplasm, or mechanical obstruction, and has a prevalence of about 10% in adults over 50 years of age. 7 In both cLDO and aLDO, the lacrimal duct system becomes a stagnant pool that can easily become infected by bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…What is the course of action taken by ophthalmologists in the world in case of congenital nasolacrimal duct obstruction? Ophthalmologists in Canada, Great Britain and Latin American countries recommend lacrimal duct probing for children with CNLDO only after they are 1 year old [20,21]. However, there is a lack of consensus among pediatric ophthalmologists in the US.…”
Section: When Should Intubation Of Lacrimal Ducts Be Performed?mentioning
confidence: 99%